Carboxymethyl cellulose gel membrane loaded with nanoparticle photocatalysts for hydrogen production. (21st May 2019) - Kang, Huiying; Gao, Jianping; Xie, Minhui; Sun, Yu; Wu, Fuming; Gao, Chunjuan; Liu, Yu; Qiu, Haixia
Abstract: Carboxymethyl cellulose (CMC) gel membranes were prepared by a chemical crosslinking method and an in situ method was used to load CdS nanoparticles with an average size of about 3 nm into the CMC gel. The negative ion groups in the CMC serve as strong binding sites for the metal ions and help prevent aggregation of the CdS nanoparticles during their growth process. This results in a CMC gel matrix loaded with stable and well-dispersed CdS nanoparticles (CdS-CMC). Pt co-catalyst particles were also loaded into the gel membrane to give CdS/Pt-CMC and both materials were used as photocatalysts for the production of hydrogen. The CdS/Pt-CMC catalyst with 5 wt % Pt exhibited a H2 evolution rate of 1365 μmol h −1 g −1, which is 81 times that of pure CdS. This improvement can be attributed to the separation of the CdS photo-generated electron-hole pairs. The photo-electrons are transferred to Pt and the formed aqueous H + ions are then rapidly converted to H2 . The incorporation of the photocatalyst into a gel matrix makes the photocatalyst easily recoverable which can help avoid environmental pollution caused by free CdS nanoparticles. Graphical abstract: Image 1 Highlights: Carboxymethyl cellulose (CMC) gel membrane was developed. Novel portable CMC gel membrane-based photocatalyst (CdS/Pt-CMC) are developed. Nanoparticles tightly and uniformly immobilized in CMC gel membrane. Morphology, thermal stability and mechanical properties identified. Photocatalytic hydrogen evolution rate up to 1365 μmol h −1 g −1 .